1993
DOI: 10.1002/stem.5530110311
|View full text |Cite
|
Sign up to set email alerts
|

Cell proliferation and differentiation in chemical leukemogenesis

Abstract: In tissues such as bone marrow with normally high rates of cell division, proliferation is tightly coordinated with cell differentiation. Survival, proliferation and differentiation of early hematopoietic progenitor cells depend on the growth factors, interleukin 3 (IL-3) and/or granulocyte-macrophage colony stimulating factor (GM-CSF) and their synergism with other cytokines. We provide evidence that a characteristic shared by a diverse group of compounds with demonstrated leukemogenic potential is the abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…12 This suggests the possibility of different dose schedules, different origin of recombinant antigen (bacterial versus eukaryotic source) or differences between leukemia and solid tumor patients as factors that predispose to the development of anti-GM-CSF antibodies. The origin of the immunity to GM-CSF and the consequences of this immunity in leukemia patients is not clear, although the important role of GM-CSF in normal differentiation of myeloid progenitors together with the differentiation arrest of leukemia blasts 6 suggest there might be a role of anti-GM-CSF antibodies in leukemia pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 This suggests the possibility of different dose schedules, different origin of recombinant antigen (bacterial versus eukaryotic source) or differences between leukemia and solid tumor patients as factors that predispose to the development of anti-GM-CSF antibodies. The origin of the immunity to GM-CSF and the consequences of this immunity in leukemia patients is not clear, although the important role of GM-CSF in normal differentiation of myeloid progenitors together with the differentiation arrest of leukemia blasts 6 suggest there might be a role of anti-GM-CSF antibodies in leukemia pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that GM-CSF is involved in the autocrine or paracrine induction of proliferation of acute myeloid leukemia (AML) cells, 1 and chemicals such as hydroquinones selectively enhance clonogenic responses to GM-CSF in murine and human bone marrow (BM) cells. 6 However, GM-CSF also facilitates cell differentiation and maturation, which are usually blocked in AML. Finally, partial and complete deletion of the GM-CSF gene, including deletion of 5q31, occurs in chromosomal abnormalities, which are associated with secondary AML and myelodysplastic syndrome (MDS), 7 suggesting a complex role of GM-CSF dysregulation in leukemogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The survival and proliferation of stem and progenitor cells are controlled by multiple growth factors, or cytokines, with overlapping functions that act individually or in combination to regulate hematopoiesis. A series of studies carried out in mice and in human bone marrow cultures have shown that benzene alters cytokine production or response to cytokines in the bone marrow (27)(28)(29)(30)(31)(32)(33)(34)(35). To determine if benzene exposure affects cytokine levels measured in peripheral blood, a more accessible and acceptable tissue source than bone marrow, we evaluated a panel of cytokines in the most heavily exposed workers and a subset of controls.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiments utilizing murine HPC essentially depleted of stromal, and lineage-committed bone marrow cells suggest that the observed synergistic response to rGM-CSF represents an intrinsic effect on responding HPC and is independent of altered production of cytokines by accessory cell populations (12,13). Because HQ-induced synergism is specific for GM-CSF, the possibility that HQ pretreatment results in altered GM-CSF receptor expression was evaluated.…”
Section: Studies On the Role Ofaltered Gm-csf Receptor Expressionmentioning
confidence: 99%
“…Moreover, inhalation exposure of mice to benzene enhances clonogenic response to GM-CSF (9,10), and chronic exposure to high concentrations induces a persistent myeloproliferative disorder (10,11). These specific alterations are most likely due to hydroquinone (HQ), which selectively enhances clonogenic response to GM-CSF in murine bone marrow cells (12,13). Our work has focused on understanding the relationship between altered response of primitive bone marrow cells to cytokines involved in proliferation and survival and early events in leukemogenesis.…”
Section: Introductionmentioning
confidence: 99%